2018
DOI: 10.1016/j.ygyno.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study comparing oncologic outcomes between two nodal assessment methods in patients with deeply invasive endometrioid endometrial carcinoma: A sentinel lymph node algorithm versus a comprehensive pelvic and paraaortic lymphadenectomy

Abstract: Use of an SLN algorithm in deeply invasive EEC does not impair oncologic outcomes. Survival is excellent in node-negative cases, irrespective of assessment method. Adjuvant chemotherapy in node-negative patients does not appear to impact outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
0
55
0
3
Order By: Relevance
“…Compared to pelvic and/or para-aortic lymphadenectomy, sentinel lymph node dissection was not found to be associated with either increased length of stay or readmission. Thus, given evidence that oncologic outcomes for early stage endometrial cancer are similar when comparing lymphadenectomy versus sentinel lymph node dissection, our findings provide further rationale for pursuing sentinel lymph node dissection rather than full lymphadenectomy [34]. Last, patients with prolonged length of stay after MIS for endometrial cancer had almost three times higher risk of readmission than those patients with earlier discharge in our cohort.…”
Section: Risk Factormentioning
confidence: 59%
“…Compared to pelvic and/or para-aortic lymphadenectomy, sentinel lymph node dissection was not found to be associated with either increased length of stay or readmission. Thus, given evidence that oncologic outcomes for early stage endometrial cancer are similar when comparing lymphadenectomy versus sentinel lymph node dissection, our findings provide further rationale for pursuing sentinel lymph node dissection rather than full lymphadenectomy [34]. Last, patients with prolonged length of stay after MIS for endometrial cancer had almost three times higher risk of readmission than those patients with earlier discharge in our cohort.…”
Section: Risk Factormentioning
confidence: 59%
“…Whether aortic lymphadenectomy could have a therapeutic role is a debatable point, as well as what is the best adjuvant therapy for node-positive patients. Multicenter retrospective series have not identified differences in survival in women with endometrial cancer treated with an SLN mapping procedure or full staging lymphadenectomy 26 27. Undoubtedly having aortic nodal involvement (FIGO stage IIIC2) has a prognostic impact.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic superiority of LND over SLN mapping alone, especially in high-risk cases and those with SLN metastasis, is still highly debatable. Retrospective analyses, however, have suggested that using SLN mapping over LND does not compromise oncologic outcome in such cases [10,11]. Furthermore, SLN mapping compared with LND is associated with a much lower risk of LEL development in patients with vulvar or endometrial cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%